The Effect of e-Samsat Implementation, Tax Sanctions, and Income Level on Motor Vehicle Taxpayer Compliance in Denpasar City - Ni Putu Elia Purnama Sari; Rai Gina Artaningrum; Putu Aristya Adi Wasita (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
Tax revenue is the main source of state income that plays an important role in financing national development. One of the regional taxes that contributes significantly to Regional Original Revenue (PAD) is the Motor Vehicle Tax (PKB). However, in Denpasar City, there is still a high level of Motor Vehicle Tax arrears even though the government has implemented a digital-based payment system through Electronic Samsat (e-Samsat) and the SIGNAL application. This condition indicates that the increase in technology use has not been fully followed by an increase in taxpayer compliance. This study examines the influence of three key factors on motor vehicle taxpayer compliance in Denpasar City: the implementation of e-Samsat (Indonesia’s electronic tax payment system), tax penalties, and income levels. The e-Samsat system is expected to improve convenience and efficiency in tax payments, encouraging greater compliance. Tax penalties are considered an essential deterrent, while income level is believed to significantly affect taxpayers' ability and willingness to meet their obligations. A quantitative research approach, relying on primary data, was used. The population consisted of motor vehicle taxpayers registered with the Denpasar SAMSAT office. A total of 100 respondents were selected using accidental sampling. The data were analysed using multiple linear regression using SPSS version 25.0. The findings show that e-Samsat implementation, tax penalties, and income levels all positively affect taxpayer compliance. In other words, the easier the service, the stricter the penalties, and the higher the income, the more likely taxpayers are to comply with their motor vehicle tax obligations.